2008
DOI: 10.1007/s10577-008-1220-z
|View full text |Cite
|
Sign up to set email alerts
|

Pairing and synapsis in wild type Arabidopsis thaliana

Abstract: A spreading technique was used to perform a structural analysis of prophase I nuclei in pollen mother cells (PMCs) of wild-type Arabidopsis thaliana. In leptotene, all chromosomes developed fully axial elements before a presynaptic alignment was observed. Pairing and synapsis start in regions close to the telomeres at early zygotene. Interstitial synaptonemal complex (SC) stretches were found to occur at several sites per bivalent at mid zygotene. Within individual bivalents, extensive regions of SC formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…1 C) [Anderson et al, 2003;Lopez et al, 2008]. Serial sections can be used to analyze the nucleus in 3 dimensions [Gillies, 1973].…”
Section: Imaging Methods For Studying Chromosome Dynamics In Meiotic mentioning
confidence: 99%
See 2 more Smart Citations
“…1 C) [Anderson et al, 2003;Lopez et al, 2008]. Serial sections can be used to analyze the nucleus in 3 dimensions [Gillies, 1973].…”
Section: Imaging Methods For Studying Chromosome Dynamics In Meiotic mentioning
confidence: 99%
“…However, 3D reconstruction of fine sections is very difficult and laborious and, therefore, this method is not well suited for analyzing rapid chromosome dynamics. For this reason most studies on meiotic chromosomes in plants using EM have been done with the spreading technique [Gillies, 1981;Anderson et al, 2003;Lopez et al, 2008]. Antibodies coupled with gold particles can be used for protein immunolocalization in EM [Anderson et al, 1997;Lohmiller et al, 2008] although, inevitably, the number of different antibodies that can be used at the same time is very limited.…”
Section: Imaging Methods For Studying Chromosome Dynamics In Meiotic mentioning
confidence: 99%
See 1 more Smart Citation
“…The synaptonemal complex spreads were prepared according to the protocol described by López et al (2008) with minor modifications: 0.05% (v/v) Triton X-100 + 0.1% (v/v) Lipsol detergent was included in the swelling medium. The slides were stained with aqueous AgNO 3 (40%, w/v) at 45°C and examined under an electron microscope (Jeol 1010).…”
Section: Electron Microscopymentioning
confidence: 99%
“…Almost all crossovers detected in the construction of genetic maps of rye, wheat and barley concentrate in the distal half of the chromosome arms Lukaszewski, 1992;Lukaszewski and Curtis, 1993;Gill et al, 1996a, b;Künzel et al, 2000;Saintenac et al, 2009]. The ultrastructural analysis of SC formation demonstrated that the commencement of pairing at distal sites and succession by numerous intercalary initiations is common to many plant species, regardless of the distribution of chiasmata [Gillies, 1975[Gillies, , 1985Holm, 1977Holm, , 1986Albini and Jones, 1987;Martínez et al, 2001a, b;López et al, 2008].…”
mentioning
confidence: 99%